Indels, CNVs and the spectrum of human genome variation - Levy, Samuel (Henry Stewart Talks, 2009)
Long term goals for human genotype-phenotype studies, De novo assembly of an individual genome sequence, How does HuRef compare to other human assemblies?, SNP in HuRef assembly, How do variants impact coding sequence?, Nucleotide diversity, Homozygous insertions and deletions: identification and validation, CNVs and read depth coverage, Construction of haplotypes and diploid representation, Additional sequencing to provide complete genome assembly through detection of indels/CNV
Archived at 2021/02/25